Develop a plan for scout activities in educational institutions Lamphun Technical College - Tananchai, Tantawan; Channoi , Pronnipa (MCU Haripunchai Review, 2025)
This study aimed to 1) study the method of making a non-formal scout activity plan in an educational institution, Lampang Technical College, 2) to make a non-formal scout activity plan in an educational institution, Lampang Technical College, 3) to evaluate the results of using the non-formal scout activity plan in an educational institution, Lampang Technical College. The groups of informants were experts, school administrators, and teachers, who were selected by purposive sampling. The instruments used in the study were 1) tools for development, including focus group discussion topics and questionnaires for assessing appropriateness. 2) tools for evaluating the development results, including (1) a questionnaire on the results of using the scout activity plan. Data were analyzed by finding the mean percentage, standard deviation, and content analysis. The results of the study are as follows: 1) the important steps in making a plan for Boy Scout activity in educational institutions consist of 1) setting the activity goals, 2) selecting the activity, 3) planning the implementation, 4) evaluating the activity, and 5) making the activity report. 2) The result of making a plan for Boy Scout activity in educational institutions, Lampang Technical College, consisted of 4 components: 1) Introduction, 2) Educational institution curriculum structure, 3) Course description, and 4) Evaluation. Overall, the informants had the highest level of opinion (µ = 4.90, σ = 0.08) 3) The result of evaluating the use of the plan for Boy Scout activity in educational institutions, Lampang Technical College, all 4 components were at a high level.